Phloroglucinol in plant tissue culture - Teixeira da Silva, Jaime A; Dobránszki, Judit; Ross, Silvia (In vitro cellular & developmental biology. Plant, 2013)
In plant tissue culture research, there is a constant need to search for novel substances that could result in better or more efficient growth in vitro. A relatively unknown compound, phloroglucinol (1,3,5-trihydroxybenzene), which is a degradation product of phloridzin, has growth-promoting properties. Phloroglucinol increases shoot formation and somatic embryogenesis in several horticultural and grain crops. When added to rooting media together with auxin, phloroglucinol further stimulates rooting, most likely because phloroglucinol and its homologues act as auxin synergists or auxin protectors. Of particular interest is the ability of phloroglucinol—a precursor in the lignin biosynthesis pathway—to effectively control hyperhydricity through the process of lignification, thus maximizing the multiplication rate of woody species and other species that are difficult to propagate. Phloroglucinol has also been used to improve the recovery of cryopreserved Dendrobium protocorms, increasing the potential of cryopreservation for application in ornamental biotechnology. Phloroglucinol demonstrates both cytokinin-like and auxin-like activity, much like thidiazuron, and thus has considerable potential for application in a wide range of plant tissue culture studies.